Inference and due motivation in the indiciary evidence. Can the use of the maximum of experience in judicial argumentation be rational controlled? - Sahuanay Calsín, Octavio César (2016)
The article discusses the everlasting problem of the search for the truth in the criminal law, from philosophical, epistemological, logical edges, and from procedural science; to go then shortening the framework up to the particular test — currently the reigning evidence of evidentiary law — and lands on inference, which is the soul of the proof by evidence. In the same line of approach, emphasis is placed on describing the difficulties of the inferential process when using the experience rules: the lack of harmony and uniqueness of the experience rule should be approached with scientific rigor and, finally, an approach is attempted to systematize its use in the judicial reasoning.